THE IMPORTANCE OF GRAMMAR IN LEARNING MODERN RUSSIAN - Yugay Milana Gennadevna (Bright Mind Publishing, 2025)
The article analyzes a general approach to the grammatical rules and exceptions of the Russian language, as well as the learning methods developed by several scholars who have made significant contributions to the field of linguistics. To achieve this goal, the article uses traditional and modern approaches to the study of Russian grammar. The article also discusses the importance of grammatical skills and competence in learning Russian.
Keywords: Russian language, syntax, elements, set, education, word, content, tool, dictionary, system, language, rule, learning, application, competence.